PENGUNGKAPAN AKTIVITAS GREEN SUPPLY CHAIN MANAGEMENT PADA PERUSAHAAN KATEGORI EMAS PROPER 2013 – 2014 - Temy Setiawan (Universitas Bunda Mulia, 2017)
The problems with the environment which has grabbed the public attention is the main reason for the development of green supply chain management.Companies need to take parts in this continuous development. One efforts which has been done is to disclose of environmental activities in sustainable reporting.This research is aimed to explore the information of companies’ activity in relation to environmental issues. This research classifies the criteria of green supply chain management into 4 categories : green purchasing; eco design; reverse logistic and regulator.This is a qualitative research. The researcher conducts an analysis on 6 companies listed in 2013 PROPER with gold predicate.This research finds that the most common activities conducted by the companies in taking their responsibilities to the environment is legislation and regulator pressure andPT. Medco E&P Indonesia which has devoted most of their activities to environmental issues. All of the company has achieved the environmental performance and few companies have increasing net income.There is a very limited research focused on companies activities as related to green supply chain management. This research will explain the specific environmental activities in which companies are focused on in responding the green supply chain management.Keywords :green supply chain management; green purchasing; eco design; reverse logistic and regulator.